Genome-wide association study of resistance to Mycobacterium tuberculosis infection identifies a locus at 10q26.2 in three distinct populations - Quistrebert, Jocelyn; Orlova, Marianna; Kerner, Gaspard; Ton, Le Thi; Luong, Nguyễn Trong; Danh, Nguyễn Thanh; Vincent, Quentin B.; Jabot-Hanin, Fabienne; Seeleuthner, Yoann; Bustamante, Jacinta; Boisson-Dupuis, Stéphanie; Huong, Nguyen Thu; et al. (PLoS genetics, 2021)
The natural history of tuberculosis (TB) is characterized by a large inter-individual outcome variability after exposure to Mycobacterium tuberculosis . Specifically, some highly exposed individuals remain resistant to M . tuberculosis infection, as inferred by tuberculin skin test (TST) or interferon-gamma release assays (IGRAs). We performed a genome-wide association study of resistance to M . tuberculosis infection in an endemic region of Southern Vietnam. We enrolled household contacts (HHC) of pulmonary TB cases and compared subjects who were negative for both TST and IGRA (n = 185) with infected individuals (n = 353) who were either positive for both TST and IGRA or had a diagnosis of TB. We found a genome-wide significant locus on chromosome 10q26.2 with a cluster of variants associated with strong protection against M . tuberculosis infection (OR = 0.42, 95%CI 0.35–0.49, P = 3.71×10 −8 , for the genotyped variant rs17155120). The locus was replicated in a French multi-ethnic HHC cohort and a familial admixed cohort from a hyper-endemic area of South Africa, with an overall OR for rs17155120 estimated at 0.50 (95%CI 0.45–0.55, P = 1.26×10 −9 ). The variants are located in intronic regions and upstream of C10orf90 , a tumor suppressor gene which encodes an ubiquitin ligase activating the transcription factor p53. In silico analysis showed that the protective alleles were associated with a decreased expression in monocytes of the nearby gene ADAM12 which could lead to an enhanced response of Th17 lymphocytes. Our results reveal a novel locus controlling resistance to M . tuberculosis infection across different populations.